2021
DOI: 10.1108/cc-06-2020-0018
|View full text |Cite
|
Sign up to set email alerts
|

The 100 most-cited articles on malaria: a bibliometric analysis

Abstract: Purpose The use of citation analysis to identify the first 100 articles on malaria offers unique insights into understanding the disease and subsequent follow-up treatment innovations over time. In this study, the 100 most-cited articles on malaria were analyzed, and key studies were highlighted. Design/methodology/approach The data of the most-cited articles for the period of four decades were extracted from the Web of Science database. The search terms malaria, plasmodium infection and remittent fever were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 55 publications
0
2
0
Order By: Relevance
“…Although a few bibliometric studies on malaria are reported, they were either restricted to a particular geography (Latin America [ 4 ]; China [ 5 , 6 ]; India [ 7 , 8 ]; Malawi [ 9 ]; Portugal [ 10 ]; Central African Republic [ 11 ]), a particular period or a specific context related to malaria (artemisinin [ 12 , 13 ]; malaria vaccines [ 14 ]; malaria in pregnancy [ 15 ]; malaria vector resistance [ 16 ]; anti-malarial drug resistance [ 17 ]; citations [ 18 , 19 ]) or to a wider term such as mosquito-borne disease [ 20 ] or parasitology [ 21 ]. There was only one article that analysed global research on malaria [ 22 ] but it was focused on Plasmodium vivax and the data were retrieved only from the Scopus ® .…”
Section: Introductionmentioning
confidence: 99%
“…Although a few bibliometric studies on malaria are reported, they were either restricted to a particular geography (Latin America [ 4 ]; China [ 5 , 6 ]; India [ 7 , 8 ]; Malawi [ 9 ]; Portugal [ 10 ]; Central African Republic [ 11 ]), a particular period or a specific context related to malaria (artemisinin [ 12 , 13 ]; malaria vaccines [ 14 ]; malaria in pregnancy [ 15 ]; malaria vector resistance [ 16 ]; anti-malarial drug resistance [ 17 ]; citations [ 18 , 19 ]) or to a wider term such as mosquito-borne disease [ 20 ] or parasitology [ 21 ]. There was only one article that analysed global research on malaria [ 22 ] but it was focused on Plasmodium vivax and the data were retrieved only from the Scopus ® .…”
Section: Introductionmentioning
confidence: 99%
“…Although a few bibliometric studies have been performed on research related to malaria, ours is a first analysis of this kind as its targets global malaria bibliometric research through three different databases. Previously published bibliometric malaria-related research was either restricted to a particular geography (Latin America -Munoz-Urbano et al, 2014; China – Fu et al, 2015, Du et al, 2021; India – Singh and Mahanty, 2019, Gupta and Bala, 2011; Malawi – Mwendera et al, 2017; Portugal – Ferreira and Teixeira, 2019; Central African Republic - Nzoumbou-Boko et al, 2022), a particular period or a specific context related to malaria (artemisinin – Dong et al, 2022, Xu et al, 2018; Yao et al, 2012; malaria vaccines – Garg et al, 2009; malaria in pregnancy - van Eijk et al, 2012; malaria vector resistance – Sweileh et al, 2016; anti-malarial drug resistance - Sweileh et al, 2017; citations - Ghamgosar, Zarghani, and Nemati-Anaraki, 2021, Kolle, Vijayashree, and Shankarappa, 2017) or to a wider term such as mosquito-borne disease (Ong, Pauzi, and Gan, 2022) or parasitology (Ellis et al, 2020) or even COVID-19 (Mala et al, 2022). We could find only one article that analyzed global research on malaria (Garrido-Cardenas et al, 2019) but this article was focused on P. vivax and only from the Scopus database.…”
Section: Discussionmentioning
confidence: 99%